Factor VIII S373L: Mutation at P1’ Site Confers Thrombin Cleavage Resistance, Causing Mild Haemophilia A - Johnson, D J D; Pemberton, S; Acquila, M; Mori, P G; Tuddenham, E G D; O'Brien, D P (Thrombosis and Haemostasis, 1994)
A novel CRM+ mutation, factor VIII position 373 serine to leucine substitution (FVIII 373-Leu) was identified during a survey of Factor VIII (FVIII) mutations. We have purified the variant protein from the patient's plasma in order to allow further characterisation of the molecule. The CRM+ plasma contained 120% Factor VIII antigen (FVIILAg) and 6% Factor Vili coagulant activity (FVIILC). After purification the mutant FVIII was subjected to thrombin proteolysis, and was thereby activated 5.6-fold compared with 7-fold for wild type molecule. Subsequently, spontaneous inactivation of the mutant was much slower than noted for wild type FVIII. Western blot analysis using monoclonal antibodies demonstrated that thrombin cleavage of FVIII 373-Leu at positions 740 and 1689 were normal but that cleavage at position 372 was completely absent.Crystallographic coordinates of the active site of thrombin complexed to fibrinopeptide A were used to explore possible mechanistic reasons for the failure of thrombin to cleave the mutant FVIII at position 372. Steric hindrance between the mutant side chain and the side chain of the PI residue was apparent. We conclude that the functional defect of FVIII 373-Leu results from the inability of thrombin to cleave the mutant at position 372-373, and propose that this is due to steric hindrance by the side chain of leucine 373, preventing correct formation of the enzyme substrate complex.